Requirement Model of Rubber Trading on Android Operating System - Homhual, Podjana; Metaweesuwan, Sasiporn; Suksawang, Pramhathai; Sirikhamhom, Amon (International Journal of Engineering and Technology, 2018)
The objective of this research is to design and develop a mobile application on android operating system for rubber trading and also to study the user satisfaction with mobile application on android operating system for rubber trading. The target population for this research is a group of people who has been involved in rubber trading. There are 50 users by means of purposive sampling. The statistical methods for analysis are in terms of mean and standard deviation. This research has been tapped into the systems development life cycle to carry out the operation with 6 functions as registration, login, customer information management, rubber price information management, management of rubber trading information and report. The development using android SDK on a mobile phone operating system, Android 5.0 or higher. And is built using Android Studio and Java Development Kit (JDK) as the programing language. From this research, it was found that the overall evaluation is the high levels (= 4.38, S.D. = 0.73). The results of the evaluation of the performance of applications by experts. And satisfaction of the users that have the same opinions. It is that developed applications are of acceptable quality. Usability is as the degree to which application can be used by people to meet their needs. It is easy to find and store data in a systematic. This application can help reduce the cost and new channel for customers or users to track data.
Keywords: Mobile applications; android operating system; rubber trading.